2008
DOI: 10.1097/iae.0b013e3181619bee
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Doses of Intravitreal Bevacizumab (Avastin) for Treatment of Macular Edema Secondary to Branch Retinal Vein Occlusion

Abstract: There were no statistically significant differences between the two dose groups with regard to the number of injections and anatomical and functional outcomes. Intravitreal injection of bevacizumab at doses up to 2.5 mg appears to be effective in improving BCVA and reducing CMT in BRVO in the short term. Multiple injections are needed in a large number of eyes for continued control of macular edema and preservation of visual acuity in the short term. Longer studies are needed to determine what role if any intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 27 publications
4
61
0
2
Order By: Relevance
“…Consequently, there have been other reports of short-term beneficial effect of intravitreal bevacizumab to treat macular oedema secondary to retinal vascular disease, including branch retinal vein occlusion 24,25 and diabetic retinopathy. 26,27 More recently, Ferrara et al 28 reported a dramatic improvement in the visual acuity and clinical fundus appearance with significant macular thickness reduction after the early intravitreal bevacizumab injections.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there have been other reports of short-term beneficial effect of intravitreal bevacizumab to treat macular oedema secondary to retinal vascular disease, including branch retinal vein occlusion 24,25 and diabetic retinopathy. 26,27 More recently, Ferrara et al 28 reported a dramatic improvement in the visual acuity and clinical fundus appearance with significant macular thickness reduction after the early intravitreal bevacizumab injections.…”
Section: Discussionmentioning
confidence: 99%
“…Doses of bevacizumab used in the literature have ranged from 1.25 to 2.5 mg. 10,11,20,21 We chose the higher dose of 2.5 mg in this study in the hopes of prolonging the therapeutic effect and reducing the number of repeated injections. The average number of injections in this study was 1.4 in a 6-month follow-up.…”
Section: Figmentioning
confidence: 99%
“…In several clinical studies bevacizumab, one of anti-VEGF agent, was reported to significantly reduce ME and improve visual function in BRVO. [10][11][12] However, its half-life in vitreous is as short as 4.32 days and its effective concentration is maintained for 30 days, thus multiple injection is usually required for maintaining its effect. 13 Multiple injections of bevacizumab increase the risk of injection-related complications such as vitreous hemorrhage, retinal detachment, and endophthalmitis, and it can be an economic burden to patients.…”
Section: Introductionmentioning
confidence: 99%